ARF7 increases the endogenous contents of castasterone through suppression of BAS1 expression in Arabidopsis thaliana. (February 2016) - Youn, Ji-Hyun; Kim, Min Kyun; Kim, Eun-Ji; Son, Seung-Hyun; Lee, Ji Eun; Jang, Mun-Seok; Kim, Tae-Wuk; Kim, Seong-Ki
Graphical abstract: The regulation of BAS1 expression through interaction between BZR1 and ARF7 contributes to the maintenance of brassinosteroid homeostasis in A. thaliana. Highlights: Expression of the brassinosteroid (BR)-inactivating BAS1 gene is suppressed by ARF7. Suppression of BAS1 expression by ARF7 leads to increase the endogenous level of BR in Arabidopsis . ARF7 interaction with BZR1 inhibits their DNA binding activity and regulation of BAS1 expression. Abstract: Homeostasis of brassinosteroids (BRs) maintained by the balance between their biosynthesis and inactivation is important to coordinate the diverse physiological and developmental responses of plants. Although BR signaling regulates the endogenous levels of BRs via negative feedback regulation, it remains largely unknown how the biosynthesis and inactivation of BR are triggered. BAS1 encodes CYP734A1, which inactivates the biologically active BRs via C-26 hydroxylation and is down-regulated by a BR-responsive transcription factor, BZR1. Here it is demonstrated that the expression of the BAS1 gene is regulated by auxin response factors (ARFs) in Arabidopsis thaliana . Two successive E-box motifs on the BAS1 promoter function as BZR1 binding sites and are essential for BR-regulated BAS1 expression. The expression of BAS1 is increased in the arf7 and arf7arf19 mutants. The endogenous level of bioactive BR, castasterone, is greatly decreased in those mutants. ARF7 can bind to the E-box motifs of the BAS1 promoter where BZR1 binds, suggesting that ARF7 and BZR1 mutually compete for the same cis -element of the BAS1 promoter. Additionally, ARF7 directly interacts with BZR1, which inhibits their DNA binding activities and regulation of BAS1 expression. In conclusion, auxin signaling via ARF7 directly modulates the expression of BAS1 by competition with BZR1, thereby increasing the level of castasterone and promoting growth and development in A. thaliana.